Relationship between workplace friendship and organizational commitment - Teimouri, Misha (2011)
The main objective of this study is to determine the nature of relationship between workplace friendship and organizational commitment in two Iranian organizations. Data collected via a questionnaire survey of 302 employees from an Iranian delivery service company and a milk products company. Workplace friendship and multi-dimensional of organizational commitment scales, created by Neilson (2000) and Mayer & Allen (1997) was used to ask respondents about their perception of workplace friendship and organizational commitment.Data obtained were analyzed using the SPSS software version 16. The relationship between two dimensions of workplace friendship, which is including of Friendship Prevalence and Friendship Opportunity, and three components of organizational commitment (Affective, Continuance, and Normative Commitment) were examined using the Spearman Rho correlation.The findings indicate that the level of Organizational Commitment and Workplace Friendship are rather high among the administrative staff of the two companies. The study shows that Friendship Opportunity is positively related to Normative Commitment.Continuance Commitment and Friendship Prevalence are found to be significantly related to Affective Commitment, Normative Commitment, and Continuance Commitment. The result demonstrated that the relationship between friendship dimensions and Normative Commitment is higher than the Continuance Commitment and Affective Commitment. However, there is no significant relationship between Friendship Opportunity and Affective Commitment. The overall pattern in the relationship suggested that workplace friendship has a significant influence on organization commitment among the respondents. The findings of this study implicate that managers in Iranian companies need to pay serious attention and effort to create a friendly environment that encourages commitment among the employees in their organizations. It is obvious from this study that the opportunity to form friendships may have resulted in positive work attitude in organizational commitment. This study concludes that workplace friendship is becoming a more significant issue in the organizational environment since it relates very closely to how individuals operate in teams and organizations as a whole. As such, the need for further and more direct research is vital to understand the effect of workplace friendship as a phenomenon.